Assessing Visceral Obesity and Abdominal Adipose Tissue Distribution in Healthy Populations Based on Computed Tomography: A Large Multicenter Cross-Sectional Study - Kong, Ming; Xu, Manman; Zhou, Ying; Geng, Nan; Lin, Ning; Song, Wenyan; Li, Shanshan; Piao, Yuetong; Han, Zuoqing; Guo, Rong; Yang, Chao; Luo, Nan; et al. (Frontiers in Nutrition, 2022)
Objective: Abdominal adipose is closely related to many endocrine and metabolic diseases. The aim of this study was to analyze the distribution of abdominal adipose in a healthy population in northern China determined by abdominal computed tomography (CT). Methods: Data for this study were obtained from a multicenter, retrospective, cross-sectional study that collected abdominal CT scans of 1787 healthy individuals from 4 representative cities in northern China. Areas of visceral adipose tissue(VATA) and subcutaneous adipose tissue(SATA) were obtained by measuring CT images at the level of the 3rd lumbar vertebra. Visceral adipose tissue index(VATI) and subcutaneous adipose index(SATI) were obtained by normalizing the square of height to analyze the distribution of the above indexes and visceral obesity among different body mass index (BMI), gender and age. Results: The mean age of this healthy population was 45.3±15.2 years and the mean BMI was 23.5 ± 3.2 kg/m2, with 902 men and 885 women. Compared with women, men had a significantly higher median VATA((120.9 vs 67.2 cm2), VATI(39.1 vs 25.6 cm2/m2) and a significantly higher percentage of visceral adiposity (VATA ≥ 100 cm2) (60.8% vs 30.4%). While women had signiﬁcantly higher SATA (116.9 vs 146.7 cm2) and SATI(38.8 vs 55.8 cm2/m2) than men. Whether men or women, VATI was positively correlated with age. Interestingly, SATI was weakly positively correlated with age in women, while SATI was weakly negatively correlated with age in men. In persons with a normal BMI, the proportion of visceral adiposity increases with age, whereas in men with a normal BMI, the proportion of visceral adiposity decreases after the age of 60 years but remains greater than 50%. Conclusions: The distribution of abdominal visceral and subcutaneous adipose tissue parameters measured by CT differed among gender, age, and BMI. Even men and women with normal BMI have a high proportion of visceral obesity.